The Effect of Organizational Justice on Desire to Change Jobs: Organizational Citizenship Behavior (OCB) as a Variable - Muhammad Afif Setiawan; Majang Palupi (CV. Syntax Corporation Indonesia, 2022)
Human resource management is an important task that must be performed on an ongoing basis. Part of the reason is that human resources are fundamental to driving business growth. This study aims to examine and analyze the effect of organizational justice on the desire to change jobs mediated by Organizational Citizenship Behavior (OCB). The study was conducted on employees of a manufacturing company located in Cikarang, Bekasi Regency with a total sample of 59 respondents. Data was collected by distributing questionnaires with a Likert Scale of 1-6. Data analysis using quantitative method PLS-SEM (Partial Least Square-Structural Equation Modeling) with the help of Smart PLS software. The results showed that procedural justice had a negative and significant effect on the desire to change jobs. Interactional justice has a positive and significant effect on the desire to change jobs. Distributive justice and procedural justice both have a positive and significant effect on OCB, but not on interactional justice which shows a positive and insignificant effect on OCB. OCB has a negative and significant effect on the desire to change jobs. OCB also proved unable to mediate the relationship of the three dimensions of organizational justice (distributive justice, procedural justice and interactional justice) to the desire to change jobs.